Reliability of online pregnancy-related information and associated feelings of worry among expectant women in Qatar - Ayman Al-Dahshan (8962568) (2022)
Background Although the internet can be a source of reassurance and clarification for expectant women, it could cause concerns or feelings of worry when reading about pregnancy-related information. This research study sought to assess feelings of worry and perceived reliability of online pregnancy-related information and the associated factors among expectant women attending antenatal clinics at primary healthcare centers in Qatar. Methods A cross-sectional study design was used. The participants were recruited through a systematic random sampling technique. A self-administered questionnaire was used to collect data from the participants. Descriptive and analytic statistics were used as appropriate. Results A total of 327 expectant women completed the questionnaire. Most were aged between 26–34 years (74.1%), held a college/university degree (76.4%), and were multigravidas (73.1%). About one-third of the women (31.2%) reported feeling worried due to information they read online. They coped with these feelings by consulting their antenatal care provider at their next appointment (51.0%) or by talking with relatives and friends (47.0%). Most participants (79.2%) considered online pregnancy-related information to be reliable or highly reliable. Holding a college/university degree and being primigravidae were factors significantly associated with a high perception of reliability of online pregnancy information. Conclusion Although online pregnancy information caused feelings of worry for some expectant women, most perceived such information to be reliable. Thus, antenatal care providers should guide expectant women on how to access high-quality web-based information. Other Information Published in: BMC Pregnancy and Childbirth License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12884-022-04457-w